1995
DOI: 10.1007/bf01322441
|View full text |Cite
|
Sign up to set email alerts
|

Incipience of quantum chaos in the spin-boson model

Abstract: The peculiar spectral properties of the spin-boson model make it suitable for an investigation of quantum nonintegrability effects and level statistics from a new perspective. For fixed spin quantum number s, its energy spectrum consists of 2s + 1 sequences of levels with no upper bound. These sequences are identified and labelled consecutively by means of a quantum invariant calculated from the time average of a non-stationary operator. For integrable cases, level repulsion (on the energy axis) is limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 12 publications
6
37
0
Order By: Relevance
“…Related phenomena have been observed in particle systems by Bohigas, Tomsovic, and Ullmo [15]. In a study of the spin-boson model the observed "resonance phenomena" can be attributed to the presence of small denominators becoming more or less effective in representations of different dimensions [16]. An analytic study of these numerically observed effects in the vein of the present paper is under way [17].…”
Section: A Summary and Outlooksupporting
confidence: 59%
“…Related phenomena have been observed in particle systems by Bohigas, Tomsovic, and Ullmo [15]. In a study of the spin-boson model the observed "resonance phenomena" can be attributed to the presence of small denominators becoming more or less effective in representations of different dimensions [16]. An analytic study of these numerically observed effects in the vein of the present paper is under way [17].…”
Section: A Summary and Outlooksupporting
confidence: 59%
“…This type of resonances and their impact on the level statistics have been investigated more systematically in a recent study of the spin-boson model. [17] The numerical evidence for the nonintegrability of a classical two-spin system as derived, for example, from a Poincaré map or a strange invariant-surface, is virtually unmistakable if carried out with sufficient circumspection, even though it is not rigorous. Formal proofs of nonintegrability are scarce, essentially limited to systems that are as non-generic as integrable ones are.…”
Section: B Integrable Two-spin Systemmentioning
confidence: 99%
“…Under these conditions, the coefficients h n vanish for n > N. The Heun function thus truncates to N terms. Applying the conditions (84) and (85) in this way leads to Judd's isolated exact solutions, with a finite set of recurrence relations following from (62). The coefficients are given by…”
Section: Exceptional Pointsmentioning
confidence: 99%